Overcoming PLK1 inhibitor resistance by targeting mevalonate pathway to impair AXL-TWIST axis in colorectal cancer - Sonia Solanes-Casado (Elsevier, 2021)
New therapeutic targets are revolutionizing colorectal cancer clinical management, opening new horizons in metastatic patients’ outcome. Polo Like Kinase1 (PLK1) inhibitors have high potential as antitumoral agents, however, the emergence of drug resistance is a major challenge for their use in clinical practice. Overcoming this challenge represents a hot topic in current drug discovery research.BI2536-resistant colorectal cancer cell lines HT29R, RKOR, SW837R and HCT116R, were generated in vitro and validated by IG50 assays and xenografts models by the T/C ratio. Exons 1 and 2 of PLK1 gene were sequenced by Sanger method. AXL pathway, Epithelial-to-Mesenchymal transition (EMT) and Multidrug Resistance (MDR1) were studied by qPCR and western blot in resistant cells. Simvastatin as a re-sensitizer drug was tested in vitro and the drug combination strategies were validated in vitro and in vivo.PLK1 gene mutation R136G was found for RKOR. AXL pathway trough TWIST1 transcription factor was identified as one of the mechanisms involved in HT29R, SW837R and HCT116R lines, inducing EMT and upregulation of MDR1. Simvastatin was able to impair the mechanisms activated by adaptive resistance and its combination with BI2536 re-sensitized resistant cells in vitro and in vivo.Targeting the mevalonate pathway contributes to re-sensitizing BI2536-resistant cells in vitro and in vivo, raising as a new strategy for the clinical management of PLK1 inhibitors.